2016
DOI: 10.1016/j.canlet.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Computational pathology: Exploring the spatial dimension of tumor ecology

Abstract: Tumors are evolving ecosystems where cancer subclones and the microenvironment interact. This is analogous to interaction dynamics between species in their natural habitats, which is a prime area of study in ecology. Spatial statistics are frequently used in ecological studies to infer complex relations including predator-prey, resource dependency and co-evolution. Recently, the emerging field of computational pathology has enabled high-throughput spatial analysis by using image processing to identify differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 98 publications
0
38
0
Order By: Relevance
“…Such studies appear to suggest that the spatial organization of lymphocytic infiltration in the context of nearby cancer cells is an important prognostic hallmark of certain types of tumors. This suggests that the study of the immune response with respect to patient outcome should take into account not only the quantity of immune cells, but also the spatial arrangement of the cancerous and surrounding immune cells (20,21,23,35). Previous related studies have found a strong association between the spatial location of nuclei and surrounding cytoplasmic features with OS (20,21) and RFS (4,23) in patients with early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies appear to suggest that the spatial organization of lymphocytic infiltration in the context of nearby cancer cells is an important prognostic hallmark of certain types of tumors. This suggests that the study of the immune response with respect to patient outcome should take into account not only the quantity of immune cells, but also the spatial arrangement of the cancerous and surrounding immune cells (20,21,23,35). Previous related studies have found a strong association between the spatial location of nuclei and surrounding cytoplasmic features with OS (20,21) and RFS (4,23) in patients with early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence we can exactly extract each nucleus from the image and make it available for further analysis. For example, the features of the individual nucleus and the distribution of nuclei clusters can be used to grade and classify status of breast cancers [3,4]. Because of appearance variation such as color, shape, and texture, nuclei segmentation from histopathological images could be very challenging, as illustrated in Fig.1, in which it is very challenging even for human to recognize and segment all nuclei within the images.…”
Section: Introductionmentioning
confidence: 99%
“…cancer cells, lymphocytes and stromal cells, interact with one another. This work has demonstrated that patterns of lymphocyte infiltration are prognostic [ 10 ] and specifically that Tfh cell infiltration and gene signature predicted response in breast cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%